Effect of Tantalum Oxide Nanopowder on Heat Cure Acrylic Resin Impact Strength and Surface Hardness - yaqoub yousif , Sajjad; Saleh Abdullah , Zainab (Diyala Journal of Medicine, 2023)
Background: In elderly patients, fracture of the denture is one of the most common problems. Therefore, in this research, a chemical tantalum oxide was added to test its effect on the extent of increasing the strength of the denture and its ability to withstand fracture. Objective: To assess how Tantalum oxide affected heat – cured acrylic s impact strength and hardness. Patients and Methods: The Intention was to create a total of (60) specimens. Twenty samples were made without additives (control), and 40 had made with tantalum oxide at two different amounts ( 1%, 1.5%). Results: The impact strength tests showed highly significant difference among studied groups . The hardness test also showed really significant difference between the two groups, the controls and the experiments. when tantalum oxide had added the impact strength and hardness had increase in all concentration. Conclusion: Denture fracture in elderly patients is the main problem, while when adding this substance, a decrease in the fracture rate was observed when compared with dentures without adding this substance.